AKIBAT HUKUM PENGGABUNGAN PERUSAHAAN (MERGER) PADA PERUSAHAAN PERSEROAN TERBATAS - Suwena Putri, Wahyu; Anom Pemayun, Cokorda Istri (Kertha Semaya : Journal Ilmu Hukum, 2014)
The incorporation of the company (merger) is the incorporation of one or morebusiness entities so that from an economic standpoint is one unit, without mergingbusiness entity that joins. carried out with the aim of improving the efficiency andperformance of the company, acquiring market, reduce or inhibit competition andmaintain business continuity. The incorporation of the company (merger) has moreadvantages than disadvantages, such as cost lighter because it does not need a newlicense enterprise and more efficient. Research methods used in writing this paper is thenormative method. In order for a company to do a merger, it must first pay attention tothe interests of particular parties and the particular company must obtain approvalfrom the relevant authorities. The legal consequences of the merger (merger) of thecompany's corporate existence was ended by operation of law.
Keywords: Legal Consequences, Merging Companies, Merger